2001
DOI: 10.1073/pnas.051633498
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-ribose) polymerase-1 is required for efficient HIV-1 integration

Abstract: Poly(ADP-ribose) polymerase-1 (PARP-1; EC 2.4.2.30) is an abundant nuclear enzyme, activated by DNA strand breaks to attach up to 200 ADP-ribose groups to nuclear proteins. As retroviral infection requires integrase-catalyzed DNA strand breaks, we examined infection of pseudotyped HIV type I in fibroblasts from mice with a targeted deletion of PARP-1. Viral infection is almost totally abolished in PARP-1 knockout fibroblasts. This protection from infection reflects prevention of viral integration into the host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 57 publications
1
85
2
Order By: Relevance
“…Human Rad18 contains a putative SAP-box (39), a domain recently recognized to mediate the binding of certain proteins to specific A/T-rich DNA regions known as the scaffold attachment regions (SAR) (40). Interestingly, PARP-1, Ku antigens, and HMG-I/Y, which are involved in retroviral integration (7,12,13,41), have all been found to be SARbinding proteins (42)(43)(44). An intriguing possibility is that the molecules relevant for HIV-1 integration cluster together, perhaps in the vicinity of SARs, achieving in this way the coordination required for these complex reactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human Rad18 contains a putative SAP-box (39), a domain recently recognized to mediate the binding of certain proteins to specific A/T-rich DNA regions known as the scaffold attachment regions (SAR) (40). Interestingly, PARP-1, Ku antigens, and HMG-I/Y, which are involved in retroviral integration (7,12,13,41), have all been found to be SARbinding proteins (42)(43)(44). An intriguing possibility is that the molecules relevant for HIV-1 integration cluster together, perhaps in the vicinity of SARs, achieving in this way the coordination required for these complex reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Components of another DNA repair pathway, the base excision repair (BER), have been successfully tested in vitro for their ability to repair retroviral integration-dependent gaps (11). Poly(ADP-ribose) polymerase-1 (PARP-1), an enzyme activated by DNA strand breaks, has also been linked to the retroviral integration process (12,13). Its proposed role in chromatin decondensation would facilitate access of the repair machinery to the integration site (13).…”
Section: Integrase (In)mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies show an effect on viral integration upon loss or down regulation of known DNA repair proteins (2)(3)(4)(5)(6)(7)(8)(9). However, other studies suggest that NHEJ proteins are not important for viral integration [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…The final step is filling in these gaps in the host DNA [2]. The completion of the integration process by repairing the gapped DNA intermediates may involve a number of DNA repair proteins, including the NHEJ repair pathway [2][3][4], Poly (ADP-ribose)-polymerase (PARP) [5,6], ATM [7], ATR [8] and RAD18 proteins [9]. Our previous study demonstrated that Metnase was important for integration of free fragments of foreign DNA [1].…”
Section: Introductionmentioning
confidence: 99%